Platelet-Rich Plasma, Adipose Tissue, and Scar Modulation. (30th March 2018) - Sayadi, Lohrasb R; Obagi, Zaidal; Banyard, Derek A; Ziegler, Mary E; Prussak, Jordyne; Tomlinson, Luke; Evans, Gregory R D; Widgerow, Alan D
Abstract: In developed countries, over 100 million people per year form scars, of which 30% become hypertrophic. These scars are defined histologically by the presence of persistently contractile myofibroblasts. Recent in vitro research suggests that certain bone morphogenic proteins (BMP) can induce scar myofibroblast dedifferentiation and reprogramming into adipocytes. Since platelets contain BMPs within their granules, it is possible that platelet-rich plasma (PRP) can act as a vehicle to deliver BMP to sites of scarring or potential scarring. Additionally, when PRP is mixed with fat graft tissue, synergistic adipogenic growth factors (including BMPs) are released which can help complete myofibroblast transformation and adipogenesis. The aim of this article is to corroborate these findings by systematically reviewing articles demonstrating the following concepts: (1) the effect of PRP on scar modulation; (2) the extraction of BMP from PRP; (3) BMP-induced myofibroblastic dedifferentiation; and (4) the effect of PRP on adipose-derived stem cells using the MEDLINE database. This search yielded 2830 articles, of which 38 met the inclusion criteria for this literature review. : Level of Evidence: 4